Skurdmedferd lungnameinvarpa - yfirlitsgrein um ábendingar og árangur medferdar - Vidarsdóttir, Halla; Möller, Páll Helgi; Gudbjartsson, Tómas (Læknafélag Íslands, Læknafélag Reykjavíkur, 2013)
In Iceland every third individual is diagnosed with malignant disease; cancer being the cause of death in one out of four individuals with only cardiovascular diseases being more common cause of death. Approximately one third of cancer patients are diagnosed with lung metastases making the lungs one of the most common metastatic site. In some of these patients a metastasectomy is a treatment option with the intention of improving survival. In this evidence-based review, the indications and outcome of pulmonary metastasectomy are discussed. This review is aimed at doctors within different specialties where Icelandic studies on pulmonary metastasectomy are referred to.